Preoperative saphenous and cephalic vein mapping as an adjunct to reconstructive arterial surgery. - Seeger, J M (1987)
B-mode ultrasound was prospectively evaluated for its ability to preoperatively assess the adequacy of venous conduit for arterial reconstruction. Fifty-one patients who had lower extremity revascularization had real-time imaging of the saphenous and cephalic veins. Veins were judged adequate based on size, compressibility, and absence of sclerosis or intraluminal echoes. All mapped veins were explored and assessed by the standard criteria for suitability. Vein size was determined from completion angiograms, and wound complications recorded and compared with patients who had similar procedures in the 12 months before the use of vein mapping. Preoperative mapping was found to be accurate in 50 to 51 patients (98%). Vein size as determined by B-mode ultrasound correlated well with angiograms, R = 0.8539 overall with R greater than 0.9 in the last 7 months of the study. Wound complications occurred in 2% of the patients who had preoperative mapping and in 17% of the historic controls. Preoperative vein mapping using B-mode ultrasound is an accurate method of determining vein suitability for use in arterial reconstruction. It improves operative planning and can contribute to a reduction in wound complications. Veins determined to be unusable by preoperative scanning need not be explored.